Contribuições da psicanálise para o trabalho com bebês e suas famílias em unidade neonatal - Araújo, Fernanda Carolina Santos (2023)
According to the World Health Organization, up to 30 million newborns around the world require some level of hospitalization each year for various reasons, whether due to complications of prematurity, bacterial infections, or congenital conditions. The hospitalization affects the psychological and financial health of family members, which can have harmful effects on the social and cognitive development of babies. Therefore, attention to the psychological and social aspects of newborns and their families is essential. With a view to this problem, this research is a systematic literature review from 2012 to 2022, aiming to answer the contributions of psychoanalysis works with babies admitted to the Neonatal Unit (NU) and their families. The following databases were consulted: Scientific Electronic Library Online (Scielo), Virtual Health Library (BVS), Portal de Periódicos da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (Capes) and Catálogo de Teses e Dissertações da Capes. The descriptors used were: "intervention" and "newborn" and "neonatology" and "psychoanalysis" or "observation" and "newborn" and "neonatology" and "psychoanalysis". The inclusion criteria were: theoretical works, research or experience reports, considering articles, dissertations and theses available in full and in Portuguese. Papers based on a theoretical framework other than psychoanalysis were excluded. The data was analyzed using psychoanalytic discourse analysis, through which four categories of analysis were identified: Emotional development of the baby and the relationship with their caregivers; Diseases, conditions and disabilities and their impact on the NB and their family; Psychoanalytic Methods and Interventions with babies; and Psychoanalysis and Health: social factors and their implications for the health of the baby and their family. Psychoanalytic methods and interventions with babies; and Psychoanalysis and Collective Health: social factors and their implications for the health of babies and their families. In conclusion, the work of psychoanalysis with babies, their families and the health team in the NU becomes even richer through exchanges with other disciplines that dialogue in this field. The ethical way in which psychoanalysts take the baby is focused: as a subject, with knowledge about themselves, opening up space for their story and for the family to allow themselves to be psychically invested in them. There are still few studies highlighting social issues in this context, which suggests the possibility of further research on the subject.